Exosomes: Small vesicles with big roles in cancer, vaccine development, and therapeutics - Abhimanyu Thakur; Diana Carolina Parra; Pedram Motallebnejad; Marcelo Brocchi; Huanhuan Joyce Chen (Bioactive Materials, 2022)
Cancer is a deadly disease that is globally and consistently one of the leading causes of mortality every year. Despite the availability of chemotherapy, radiotherapy, immunotherapy, and surgery, a cure for cancer has not been attained. Recently, exosomes have gained significant attention due to the therapeutic potential of their various components including proteins, lipids, nucleic acids, miRNAs, and lncRNAs. Exosomes constitute a set of tiny extracellular vesicles with an approximate diameter of 30–100 nm. They are released from different cells and are present in biofluids including blood, cerebrospinal fluid (CSF), and urine. They perform crucial multifaceted functions in the malignant progression of cancer via autocrine, paracrine, and endocrine communications. The ability of exosomes to carry different cargoes including drug and molecular information to recipient cells make them a novel tool for cancer therapeutics. In this review, we discuss the major components of exosomes and their role in cancer progression. We also review important literature about the potential role of exosomes as vaccines and delivery carriers in the context of cancer therapeutics.